Alternative Splicing Dynamics During the Lifecycle of Salvia miltiorrhiza Root Revealed the Fine Tuning in Root Development and Ingredients Biosynthesis - Li, Yajing; Di, Peng; Tan, Jingfu; Chen, Weixu; Chen, Junfeng; Chen, Wansheng (Frontiers in Plant Science, 2022)
Alternative splicing (AS) is an essential post-transcriptional process that enhances the coding and regulatory potential of the genome, thereby strongly influencing multiple plant physiology processes, such as metabolic biosynthesis. To explore how AS affects the root development and synthesis of tanshinones and phenolic acid pathways in Salvia miltiorrhiza roots, we investigated the dynamic landscape of AS events in S. miltiorrhiza roots during an annual life history. Temporal profiling represented a distinct temporal variation of AS during the entire development stages, showing the most abundant AS events at the early seedling stage (ES stage) and troughs in 45 days after germination (DAG) and 120 DAG. Gene ontology (GO) analysis indicated that physiological and molecular events, such as lateral root formation, gravity response, RNA splicing regulation, and mitogen-activated protein kinase (MAPK) cascade, were greatly affected by AS at the ES stage. AS events were identified in the tanshinones and phenolic acids pathways as well, especially for the genes for the branch points of the pathways as SmRAS and SmKSL1. Fifteen Ser/Arg-rich (SR) proteins and eight phosphokinases (PKs) were identified with high transcription levels at the ES stage, showing their regulatory roles for the high frequency of AS in this stage. Simultaneously, a co-expression network that includes 521 highly expressed AS genes, SRs, and PKs, provides deeper insight into the mechanism for the variable programming of AS.